Self-Talk Speaks Loud: A Bibliometric Dissection of Its Rise in Counseling Practices - Purwanti, Sri; Saputra, Wahyu Nanda Eka (citeus, 2025)
This study aims to map global trends in self-talk using a bibliometric approach. The data source was entirely drawn from the Scopus database, focusing on publications containing keywords related to self-talk, such as self-talk, talk, and relationship. The analysis was conducted on 960 selected documents published between 1975 and 2025. The results show a significant increase in publications since 2020, reflecting a growing need for self-talk approaches that support mental health and psychological well-being. Authors from various countries contributed differently, with the United States dominating in terms of both publication volume and citations, while developing countries such as Indonesia have begun to show significant participation. However, the findings also indicate that collaboration among researchers and institutions remains limited, highlighting the need to strengthen global scientific networks. Popular topics emerging from this study include impact, talk, self-talk, and anxiety in the context of building mental health. The results of this study make an important contribution to the understanding of mental well-being and the direction of self-talk research at the international level. They also provide a foundation for the development of counseling policies and practices that are more relevant to contemporary social needs. Furthermore, this study encourages further research that incorporates qualitative approaches to explore local contexts and the practical implementation of peace counseling more deeply. Specifically, self-talk as applied in counseling practices has become a crucial aspect in supporting mental health, and therefore its understanding and application need to be continually developed to enhance the effectiveness of counseling services across diverse cultural and social settings.